Evidence for the role of an invasive weed in widespread occurrence of phytoplasma diseases in diverse vegetable crops: Implications from lineage-specific molecular markers. (November 2016) - Cai, H.; Wang, L.C.; Yang, Z.X.; Wan, Q.L.; Wei, W.; Davis, R.E.; Zhao, Y.
Abstract: During the period from 2011 to 2013, several plant diseases repeatedly occurred in vegetable crops grown in Yuanmou County, Yunnan Province, China. Affected plants included cowpea, sword bean, string bean, tomato, lettuce, and water spinach. The diseased plants exhibited symptoms of witches'-broom growth and floral deformations, linking each disease to phytoplasmal infection. Phylogenetic and virtual RFLP analyses of the phytoplasmal 16S rRNA gene sequences amplified from DNA of diseased plants revealed that all of the individual strains present in the diverse vegetable plants were affiliated with a single ' Candidatus Phytoplasma' species (' Ca. Phytoplasma aurantifolia') and a single ribosomal subgroup (16SrII-A). While presence of subgroup 16SrII-A phytoplasma in this geographic region was reported previously, such widespread infections in diverse plant hosts are unveiled for the first time in this study. In pursuing the source of the infections, we found that areas surrounding the affected vegetable fields were extensively invaded by parthenium weeds ( Parthenium hysterophorus ); and many of the weed plants exhibited abnormal morphologies that were suspicious of, and later diagnosed with, phytoplasmal infections. Results from genotyping of 16S rRNA and lineage-specific immunodominant membrane protein genes revealed that the vegetable-infecting phytoplasmas and the parthenium weed phytoplasma belong to the same genetic lineage. The findings indicate that parthenium weed poses a substantial risk as a reservoir of phytoplasmal infection of nearby agricultural crops in the geographic region since the ecosystems of Yuanmou are insect-rich, and parthenium weed is known to attract diverse leafhoppers. Further studies are warranted to assess the impact of farmland invasions by the noxious weed and to devise practical measures for improved weed control. Highlights: Multiple crop diseases are attributed to infection by a single phytoplasma lineage. The phytoplasma also infects an invasive weed, Parthenium hysterophorus. The weed poses a risk as a reservoir for spread of the pathogen to nearby crops.